Propuesta de un plan estratégico para la compañía de transporte carga pesada transcalsa s.a. ciudad de portoviejo período 2017-2021 - Bravo Vera, Gema Estefanía (2017)
The objective of the research was to propose a strategic plan for TRANSCALSA S.A. oriented to improve the competitiveness in the organization; was implemented methods, techniques that allowed to know the external and internal factors of the company, that served in the decision making. The diagnosis was carried out to identify the current situation, where they were evaluated: Human Talent Capacity, Planning, Technical Aspects of Transport, Clients, Provider applying tools that served as administrative support through EFI matrices, SWOT, strategies that helped in a positive way in the positioning, growth of the company. In phase II a proposal was formulated with the purpose of perfecting the operational and administrative objectives, applying strategies that contribute to the service. Stage III set out a detailed action plan for the tasks to be executed in a specific time frame, using assigned budget in the achievement of activities where it was determined what, how, when, where, why and who will carry out the tasks. And finally Stage IV focused on strategic control using Deming's circle, by executing tasks that were not fulfilled in the action plan, the purpose of this tool is to keep it in the market, protect the investment and improve the quality of service. In conclusion the purpose of the proposal was to search possible strategies to obtain expected results in the process management and continuous improvement that will allow to plan, identify actions that help the quality of the service.